IMPACT OF DIGITAL PAYMENT SYSTEMS ON CUSTOMER SATISFACTION IN THE BANKING INDUSTRY: A STUDY - Agrawal, Rohan; Verma, Ashok (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The main objective of this study is to analyze the use of digital payment systems in the banking industry and its consequent impact on customer satisfaction. Digital payment systems have made financial transactions faster, safer, and convenient, thereby improving the consumer experience. This study examines these digital services’ reliability, simplicity, security, and timeliness from the customer’s perspective. The study focuses on customer satisfaction with various digital payment platforms, such as net banking, mobile wallets, UPI, and credit/debit cards. It was observed that the use of digital payment systems has not only improved customer experience but also increased the efficiency of the banking process. It is concluded through this study that consumers are more loyal to banks that provide state-of-the-art digital services. Moreover, strengthening the security and privacy aspects has been shown to increase customer satisfaction positively. The findings of this research will provide direction for banks to improve their digital services to meet customer needs better.